REKONSTRUKSI SISTEM PENGELOLAAN RUMAH DETENSI IMIGRASI MELALUI ADOPSI PENILAIAN RISIKO (RISK ASSESSMENT) PEMASYARAKATAN - Raihannul Thilal; Devina Yuka Utami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Immigration Detention Houses (Rumah Detensi Imigrasi) serve as immigration detention facilities responsible for accommodating foreign nationals subject to immigration administrative measures before deportation, repatriation, or the resolution of their immigration status. The increasing mobility of international migration and the growing complexity of immigration violations require detention management systems that extend beyond administrative procedures and incorporate comprehensive risk-based approaches. Current practice in Indonesia indicates that Immigration Detention Houses have not yet implemented an individual Risk Assessment mechanism as the basis for detainee classification. Consequently, detainees are generally managed under similar supervision standards without considering factors such as security threats, escape risks, vulnerability, behavioral characteristics, or special supervision needs. This study aims to analyze the existing management system of Immigration Detention Houses in Indonesia and formulate a reconstruction model through the adoption of the Risk Assessment system currently implemented within the Indonesian Correctional System. This research employs normative legal research using statutory, conceptual, comparative, and case approaches. Primary, secondary, and tertiary legal materials were collected and analyzed qualitatively. The findings indicate that the absence of a structured Risk Assessment system affects the effectiveness of detainee placement, supervision, and administrative decision-making because management remains largely administrative rather than risk-based. Therefore, reconstructing Immigration Detention House management through the adoption of the Correctional Risk Assessment system offers a strategic solution for improving detention governance, strengthening immigration law enforcement, enhancing human rights protection, optimizing institutional resources, and establishing a more accountable, effective, and adaptive immigration detention system capable of responding to contemporary migration challenges.